Hepatic phenotype in NBAS-associated disease: clinical course, prognostic factors and outcome in 230 patients - Peters, Bianca; Schlieben, Lea Dewi; Brennenstuhl, Heiko; Arikan, Cigdem; Bedoyan, Sarah M.; Bulut, Fatma Derya; Crushell, Ellen; Dionisi-Vici, Carlo; Drab, Ada; Fichtner, Alexander; Garcia, Aixa Gonzalez; Fry, Deanna; et al. (Liver international, 2025)
Background and Aims Since described in 2015, NBAS-associated disease has emerged as an important cause of acute liver failure (ALF) in children. We analysed the variable expression, genotype-phenotype association, outcome and prognostic factors of the hepatic involvement. Methods Individuals with biallelic pathogenic NBAS variants were recruited within an international observational study, including new and previously published patients. Results We studied 230 individuals, including 13 previously unreported patients. The liver was the most frequently affected organ (63.4%), with 41.3% experiencing at least one ALF. The median age at onset was 0.9 years, the median age at last ALF 5 years, the latest ALF occurred at 24 years. Liver crises were triggered by febrile infections and presented with highly increased hepatic transaminases. Liver involvement varied significantly between the subgroups: 91.7% of patients with infantile liver failure syndrome type 2 and 88.9% of patients from the combined subgroup (variants affecting β-propeller domain) presented with ALF, whereas SOPH (stature, optic atrophy, Pelger-Huët anomaly) patients mostly had either no liver involvement (66.4%) or persistently elevated transaminases without ALF (28%). The rate of native liver survival was 83.9%; 16 individuals underwent liver transplantation and 24 died. Conclusion Liver abnormalities are common and the leading cause of death in NBAS-associated disease. There is a clear genotype-phenotype association regarding the hepatic involvement. Liver crises occur primarily during infancy; however, early medical attention in case of febrile infections is necessary at all ages. Liver transplantation prevents ALF, but its risks must be weighed against the frequency and severity of liver crises decreasing with age.
Zuerst veröffentlicht: 28. Mai 2025
Gesehen am 10.11.2025